Design, synthesis, and anti-HIV-1 activity of 1-substituted 3-(3, 5-dimethylbenzyl)triazine derivatives. Issue 2 (April 2015) - Sakakibara, Norikazu; Balboni, Gianfranco; Congiu, Cenzo; Onnis, Valentina; Demizu, Yosuke; Misawa, Takashi; Kurihara, Masaaki; Kato, Yoshihisa; Maruyama, Tokumi; Toyama, Masaaki; Okamoto, Mika; Baba, Masanori
Background: The reverse transcriptase (RT) of human immunodeficiency virus type 1 (HIV-1) is an attractive target for the development of drugs used in the treatment of HIV-1 infection and acquired immune deficiency syndrome (AIDS). We have continued the search for novel anti-HIV-1 agents using the structure–activity relationships of the successful 1, 3-disubstituted and 1, 3, 6-trisubstituted uracil-type HIV-1 RT inhibitors. Methods: A series of new triazine analogs were synthesized using an established method. The anti-HIV-1 activities of these compounds were determined based on the inhibition of virus-induced cytopathogenicity in MT-4 cells. The cytotoxicity of the compounds was evaluated by assessing the viability of mock-infected cells. Results: Some of the compounds showed good-to-moderate activities against HIV-1, with half-maximal effective concentrations (EC50 ) in the submicromolar range. In particular, a dihydro-1-(4-aminobenzyl)triazine analog showed satisfactory anti-HIV-1 activity with an EC50 of 0.110 µM and a selectivity index (SI) of 909. Furthermore, molecular modeling analyses were performed to explore the major interactions between HIV-1 RT and potent inhibitors. These results may be important for further development of this class of compounds as anti-HIV-1 agents. Conclusion: The satisfactory anti-HIV-1 activity of triazine analogs may serve as the basis for further investigations of the behavior of this class of compounds against drug-resistant mutants.